1997
DOI: 10.1007/pl00004931
|View full text |Cite
|
Sign up to set email alerts
|

In U-937 promonocytes, misteltoe lectin I increases basal [Ca2+]i, enhances histamine H1- and complement C5a-receptor-mediated rises in [Ca2+]i, and induces cell death

Abstract: Mistletoe lectin I (ML I) from Viscum album inhibits cell growth and induces apoptosis (programmed cell death) in several cell types. Because increases in cytosolic Ca2+ concentration ([Ca2+]i) constitute a signal for the induction of apoptosis, we studied the effects of ML I on basal [Ca2+]i, receptor-mediated rises in [Ca2+]i and cell viability, using human U-937 promonocytes as model system. Treatment of U-937 cells with ML I (30-100 ng/ml) significantly increased basal [Ca2+]i. ML I (10-30 ng/ml) enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
4
1
1
Order By: Relevance
“…That process was observed in higher MLI concentrations (30-100 ng/mL) in vitro on U-937 promonocytes; however, MLI [Ca 2+ ] i raising property was also sustained in lower concentrations (10-30 ng/mL) by means of histamine H 1 -and complement C5a-induced rises up to fivefold. This effect was not observed in the case of the closely related HL-60 cell line (induction of cell death was observed but no rise in [Ca 2+ ] i mediated by H 1 receptor; Wenzel-Seifert et al 1997), which indicates distinct apoptosis regulation pathways in different cell lines (Wenzel-Seifert et al 1997;Nicotera et al 1994). It also concerns the action of MLI itself because the variability in vulnerability to MLI of different cell lines was reported.…”
Section: Lectinscontrasting
confidence: 47%
See 2 more Smart Citations
“…That process was observed in higher MLI concentrations (30-100 ng/mL) in vitro on U-937 promonocytes; however, MLI [Ca 2+ ] i raising property was also sustained in lower concentrations (10-30 ng/mL) by means of histamine H 1 -and complement C5a-induced rises up to fivefold. This effect was not observed in the case of the closely related HL-60 cell line (induction of cell death was observed but no rise in [Ca 2+ ] i mediated by H 1 receptor; Wenzel-Seifert et al 1997), which indicates distinct apoptosis regulation pathways in different cell lines (Wenzel-Seifert et al 1997;Nicotera et al 1994). It also concerns the action of MLI itself because the variability in vulnerability to MLI of different cell lines was reported.…”
Section: Lectinscontrasting
confidence: 47%
“…It also concerns the action of MLI itself because the variability in vulnerability to MLI of different cell lines was reported. For example, the treatment of THP-1 leukemia with MLI (25 ng/mL) caused an increase in [Ca 2+ ] i (Gabius et al 1992), whereas U-937 promonocytes did not react in this manner at similar MLI concentrations (Wenzel-Seifert et al 1997). That variation is also observed in the case of cytotoxic effects of MLI, e.g., the mouse macrophages are highly sensitive to the cytotoxic action of MLI , whereas the guinea pig macrophages are resistant (Metzner et al 1985).…”
Section: Lectinsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus it could be found that VAA-I (100 ng/ml)-induced apoptosis changes into increasing necrosis after 48 h (32). In cultures of U937 promonocytes, VAA-I (30–100 ng/ml) causes an increased cytosolic Ca 2+ concentration which, among other factors, is a sign of apoptosis (33). In addition, VAA-I could enhance the stimulating effect of histamine (H 1 ) and complement (C5a) on cytosolic Ca 2+ concentrations that play an accelerating role in the regulation of apoptosis.…”
Section: Biological Activity Of Mistletoe Lectin (Vaa-i)mentioning
confidence: 99%
“…In Kultur von U-937-Promonozyten bewirkt VAA-I (30±100 ng/ml) eine erho È hte zytosolische Ca 2+ -Konzentration, welche u. a. ein Signal fu È r die Apoptose ist [40]. Ausserdem konnte VAA-I die stimulierende Wirkung von Histamin (H 1 ) und Komplement (C5a) auf die zytosolische Ca 2+ -Konzentration, welche eine beschleunigende Rolle in der Apoptoseregulation spielt, versta Èrken [40]. Nicht nur Lektine mit RIP-Aktivita Èt verursachen Apoptose.…”
Section: Introductionunclassified